The potential of neural stem cell as vehicle to deliver Quercus infectoria extract to glioma cell in vitro - Tan, Suat Cheng; Lohis Balachandran,; Norhazilah Mohamad,; Kang, In Nee; Amirul Nasarudin,; Ruzi Aini Zakaria,; Hasmah Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Glioblastoma multiforme (GBM) is the most malignant subtype of brain cancer. However, current clinical treatments for GBM are limited in effectiveness and often impose additional side effects on patients. Here, we developed targeted anti-cancer therapy (TAT) using neural stem cells (NSC) as delivery agent to transport anti-cancer compounds directly to GBM in vitro. Anti-cancer active compounds: Tannic acid (TA) and gallic acid (GA) were extracted from local medicinal plant - Quercus infectoria (QI) using soxhlet technique with 100% methanol (QI-100%) or 70% methanol (QI-70%) solvent. Concentration of TA and GA measured using HPLC were 72.56 and 43.66 μg/mL in QI-100%, while in QI-70%, the concentrations were 72.41 and 43.31 μg/mL, respectively. Cytotoxicity effects of QI-100% and QI-70% on human GBM cell line (DBTRG-05MG), human NSC line (H9-hNSC) and human normal brain glial cell line (SVG-p12) (as negative control) were determined using MTT assay. Both QI-100% and QI-70% showed anti-proliferative properties against DBTRG-05MG at IC50, but not on H9-hNSC and SVG-p12. Taken together, data indicated that both QI extracts contained TA and GA which exhibit anti-proliferative effect specifically on cancerous cells only. Next, QI-treated H9-hNSC was seeded in a modified Boyden chamber for 12 h to investigate its migration capacity towards DBTRG-05MG. The result showed that H9-hNSC migrated towards DBTRG-05MG with 4-folds higher capacity compared to control. In addition, the migration of QI-100% treated H9-hNSC successfully reduced the number of DBTRG-05MG, indicating the anti-GBM potential of these cells after migration. In conclusion, NSC could be a specific anti-cancer compound delivery agent for GBM, reducing unwanted side effects on patients.